2018
DOI: 10.1177/2151459318764150
|View full text |Cite
|
Sign up to set email alerts
|

Use of Anticoagulants Remains a Significant Threat to Timely Hip Fracture Surgery

Abstract: Introduction:Hip fracture remains the biggest single source of morbidity and mortality in the elderly trauma population, and any intervention focused on quality improvement and system efficiency is beneficial for both patients and clinicians. Two of the variables contributory to improving care and efficiency are time to theater and length of stay, with the overall goal being to improve care as reflected within the achievement of best practice tariff. One of the biggest barriers to optimizing these variables is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 12 publications
2
33
2
1
Order By: Relevance
“…Several other recent studies identified approximately 9-16.6% of hip fracture patients to be anticoagulated. However, the absolute number of DOACs cases was relatively low [17][18][19][20]. In our study 9.9% were anticoagulated.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Several other recent studies identified approximately 9-16.6% of hip fracture patients to be anticoagulated. However, the absolute number of DOACs cases was relatively low [17][18][19][20]. In our study 9.9% were anticoagulated.…”
Section: Discussioncontrasting
confidence: 54%
“…Several studies found both vitamin K antagonists and DOACs delayed emergency surgery [17][18][19][20]. Patients on DOACs had similar perioperative hemoglobin change, transfusion rates and mortality compared to subjects without anticoagulants in both trochanteric -internal fixation and femoral neck -arthroplasty situations [19][20][21][22]. For DOACs surgery should therefore be reasonably delayed, until reversal agents become available [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Such findings have been reproduced multiple times within the literature. 9,20,21 Three recent retrospective studies have addressed preoperative DOAC use and early hip fracture surgery. Nineteen hip fracture patients taking DOACs and receiving surgery within 48 hours were compared to a non-DOAC case-matched control.…”
Section: Discussionmentioning
confidence: 99%
“…Average time to surgery for DOAC patients has been shown to vary from 35 hours to 66.9 hours. 9,20,21 Three recent studies have investigated the outcomes of hip fracture surgery within 48 hours in patients taking DOACs. [22][23][24] All found no difference in perioperative blood loss; however, Schuetze et al 23 found patients taking DOAC medication prior to surgery had a 3.4-fold increase in intraoperative transfusion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation